1970
DOI: 10.3126/jnps.v29i1.1595
|View full text |Cite
|
Sign up to set email alerts
|

Japanese Encephalitis in Children admitted at Patan Hospital

Abstract: This is a hospital based retrospective study, which was done in Pediatric ward of Patan hospital. Study period was one and half year (from Srawan 2063 to 2064 poush).Data were taken from discharge book of Pediatric ward, from the record section of this hospital, and from JE surveillance office, WHO, Kathmandu. All children from 1 month to 14 years ,who were admitted in Pediatric ward with symptoms of Meningitis, Meningoencephalitis and Encephalitis were included in this study and patients more than 14 years of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…Other studies have also corroborated this finding. 12,14 The present study was conducted over a two-year period (2014 and 2015), and the year-wise distribution of cases did not show any significant difference between the two years. This is in contrast to the study conducted by Bandhopadhyay et al from West Bengal, where they found a significant reduction in JE cases from 2011 to 2012, which had been attributed to better awareness, mass vaccination against JE etc.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Other studies have also corroborated this finding. 12,14 The present study was conducted over a two-year period (2014 and 2015), and the year-wise distribution of cases did not show any significant difference between the two years. This is in contrast to the study conducted by Bandhopadhyay et al from West Bengal, where they found a significant reduction in JE cases from 2011 to 2012, which had been attributed to better awareness, mass vaccination against JE etc.…”
Section: Discussionmentioning
confidence: 59%
“…8,10,12 This finding was statistically significant. Children from rural areas were found to be affected more as compared to those from urban areas.…”
Section: Discussionmentioning
confidence: 67%
“…In our study, out of 73 tested samples, 11 samples (15%) were positive for anti JEV IgM in the CSF. In previous studies done in Nepal1315, JEV was confirmed based on serum serology (anti JEV IgM) and only a few diagnoses in these studies were confirmed using CSF based anti JEV IgM. In our study, we determined the CSF anti JEV IgM which has a higher diagnostic accuracy than one point serum serology34.…”
Section: Discussionmentioning
confidence: 68%
“…JEV is endemic in the Terai (southern) region of Nepal [Figure 1] and in the densely populated Kathmandu valley131531. JEV rarely infects adults living in endemic regions presumably because of exposure to virus during childhood and subsequent immunity32.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation